Identification of Students' Misconceptions in Junior High Schools Accredited A using the Three Tier Test Instrument in Science Learning - Dyah Nawang Sari; Khairil Arif; Yurnetti Yurnetti; Azza Nuzullah Putri (Jurnal Penelitian Pendidikan IPA, 2024)
The study aims to analyze the student's misconception profile and determine the percentage of misconceptions of class VIII students on vibration, wave, and sound material. The research subjects were 159 students in three accredited A secondary schools during the full 2022–2023 semester. This research method is descriptive quantitative. Data collection method using a diagnostic test with a three-tier test. The three-tier test of 16 questions developed by Muhammad Ainal Yaqin and Linda Rahayuningsih was then modified by researchers with a reliability of 0.94 (very high). The three-tier test instrument consists of three tiers the first level is multiple choice, the second level is a choice of reasons for the first level, and the third level is a question of the level of confidence in the first and second levels. The result of the study was a student's misunderstanding of the vibration indicator being in the low category, whereas the wave magnitude indicator, wave movement, rapid wave retardation, medium sound retardance, and sound wave are in the medium category. The study concluded that the percentage of high school students in Koto Tangah district who suffered from misconceptions of vibration, wave, and sound material was 44% in the medium category.